EFFECT OF SOIL AND PLANT COVERING AS WELL AS SOWING TERM UPON FENNEL BULB NUTRITIONAL VALUE - Marzena Błażewicz-Woźniak (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
Fennel (Foeniculum vulgare var. azoricum Mill.), despite its high dietary value, is not a very popular vegetable in Poland. It bulbs constitute a low-calorie food, abundant in vitamins and mineral salts. They also contain, though in smaller amounts, the essential oil, determining the use of fennel fruit in medicine. In the field experiment with fennel growing the influence of soil mulching and flat plant shielding, as well as sowing term upon the nutritional values of two fennel cultivars, was examined. The studies covered 3 kinds of covers (covering the soil with black polyethylene film PE, covering the soil with black polypropylene unwoven PP 50 g m-2 and flat covering of plants with white unwoven PP 17 g m-2 (the controls were plots without covers), 3 sowing terms directly in the field, 2 cultivars (Rudy F1 and Zefa Fino). The applied covers did not significantly affect the nutritional value of fennel bulbs. The bulbs of plants from June sowings contained the most protein, total nitrogen and nitrate nitrogen, as compared to earlier sowing terms. The most dry matter, vitamin C, sugars,0 phosphorus and potassium were determined in fennel bulbs from May sowings. The least protein, sugars and potassium was contained in plant bulbs from April sowings. The bulbs of Rudy F1 cultivar were more abundant in protein, phosphorus and calcium than those of Zefa Fino cultivar. The cultivars did not differ in dry matter, nitrate, vitamin C, total sugars, fibre and potassium contents in the bulbs.